Latin American consensus for the treatment of focal chondral lesions of the knee - Juan Pablo Martinez-Cano; María Bautista; David Torres; Luis Fernando Amado; Alex Antezana; Carlos Palavicini Quesada; Gonzalo Rojas; Jenrry Pastor; Manuel Perez-Zabala; Manuel Mosquera (Elsevier, 2024)
Introduction: A consensus is useful for topics that can be common in clinical practice and controversial in some aspects of its treatment. Objectives: To establish a consensus among the Latin American society of arthroscopy, articular reconstruction and sports medicine (SLARD) for treating focal chondral lesions of the knee. Methods: A formal consensus was conducted among 3 groups of surgeons from SLARD with a special interest in cartilage. First, the steering group (n = 9) created a list of 21 statements on controversial topics and compiled a review of the literature for each topic. Second, the rating group (n = 19) gave a score to each statement according to their agreement with it, over 2 rounds (score: 1-9). Median scores and agreement levels were calculated and each statement was categorized as inappropriate, uncertain, or appropriate. Finally, the lecture group (n = 24) evaluated the appropriateness and clinical relevance of each statement. Results: During the first round, there was strong agreement on 5% of the statements, relative agreement on 14%, and lack of consensus on 81% of statements. After the second round, there was strong agreement on 57% of statements, with 43% having relative agreement and no statement having a lack of consensus. The lecture group approved all the statements. Conclusions: SLARD arrived at a consensus on the 21 statements proposed. This consensus includes a literature review and clinical experience, which represents the expert opinion of a society. Strong agreement was found in the advantages of using arthroscopy to diagnose chondral lesions, preinjury level as an age modification of treatment, superiority of nanofractures compared to microfractures, advantages of adding scaffolds, benefits of platelet-rich plasma in the midterm and faster return to sport with osteochondral autografts.